Recent Advances in Lung Cancer Immunotherapy: Input of T-Cell Epitopes Associated With Impaired Peptide Processing - Leclerc, Marine; Mezquita, Laura; Guillebot De Nerville, Guillaume; Tihy, Isabelle; Malenica, Ines; Chouaib, Salem; Mami-Chouaib, Fathia (Frontiers in Immunology, 2019)
Abstract Recent advances in lung cancer treatment are emerging from new immunotherapies that target T cell inhibitory receptors, such as programmed cell death-1 (PD-1). However, responses to anti PD-1 antibodies as single agents are observed in fewer than 20% of non-small-cell lung cancer (NSCLC) patients, and immune mechanisms involved in the response to these therapeutic interventions remain poorly elucidated. Accumulating evidence indicates that effective anti tumor immunity is associated with the presence of T cells directed toward cancer neoepitopes, a class of major histocompatibility complex (MHC)-bound peptides that arise from tumor-specific mutations. Nevertheless, tumors frequently use multiple pathways to escape T-cell recognition and destruction. In this regard, primary and acquired resistance to immune checkpoint blockade (ICB) therapy was associated with alterations in genes relevant to antigen presentation by MHC class I/beta-2-microglobulin (MHC-class I/2m) complexes to CD8 T lymphocytes. Among additional known mechanisms involved in tumor resistance to CD8 T-cell immunity, alterations in transporter associated with antigen processing (TAP) play a major role by inducing a sharp decrease in surface expression of MHC-class I/β2m-peptide complexes, enabling malignant cells to evade cytotoxic T lymphocyte (CTL)-mediated killing. Therefore, development of novel immunotherapies based on tumor neoantigens, that are selectively presented by cancer cells carrying defects in antigen processing and presentation, and that are capable of inducing destruction of such transformed cells, is a major challenge in translational research for application in treatment of lung cancer. In this context, we previously identified a non-mutant tumor neoepitope, ppCT16-25, derived from the preprocalcitonin (ppCT) leader sequence and processed independently of proteasomes/TAP by a mechanism involving signal peptidase (SP) and signal peptide peptidase (SPP). We also provided in vitro and in vivo proof of the concept of active immunotherapy based on ppCT-derived peptides capable of controlling growth of immune-escaped tumors expressing low levels of MHC-class I molecules. Thus, non-mutant and mutant neoepitopes are promising T-cell targets for therapeutic cancer vaccines in combination with ICB. In this review, we summarize current treatments for lung cancer and discuss the promises that conserved neoantigens offer for more effective immunotherapies targeting immune-escaped tumor variants.